The Equilibrium Principal Application to The Customary Law of Indigenous Peoples Based on Pancasila - Tijow, Lusiana Margareth; Hayat, Hayat; Azlina, Tengku Elmi (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
The principle of Equilibrium (balance) in indigenous and tribal peoples is an ethical demand considering the moral, social, and legal values prevailing in society. This concept is closely related to the communal mentality of customary law. This writing aims to understand how the principle of Equilibrium (balance) is applied to the cosmological rights of indigenous and tribal peoples as an effort to implement Pancasila values. The method used in this research is normative legal research with a statutory approach, supported by observation and interviews, then analyzed prescriptively to achieve a clear understanding of the issues discussed. This principle of balance serves as a guide for creating a balance between rights and obligations which can be realized concretely through legal and non-legal norms in the context of customary law communities. This allows various rights owned by indigenous peoples to be recognized and respected. Therefore, the government needs to prioritize Pancasila values in development and pay attention to the cosmological rights of indigenous and tribal peoples. Thus, customary law can be a means to answer various legal problems faced by the people in their daily lives in certain areas while maintaining the cosmological rights of the indigenous peoples themselves.